Secondary battery with high liquid retention capacity, preparation method of secondary battery and electric equipment
By applying the liquid-retaining coating of polyvinylidene fluoride and ketone anhydride-type thermoplastic polyimide on the corner area of the lithium-ion battery electrode assembly, the problem of insufficient retention of the electrolyte is solved, and the energy density of the battery cell is maintained and improved. The dynamic performance is achieved, and the diaphragm strength is reduced.
Patent Information
- Application Number
- CN202411488562.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-10
AI Technical Summary
During the fast charging cycle of lithium-ion batteries of 3C and above, the electrolyte is insufficient due to spatial extrusion at the corners of the winding structure, and the permeability of lithium ions decreases, making corner lithium black spots prone to occur. Existing methods such as increasing The thickness of the membrane or the use of a membrane with higher porosity will lose the energy density of the cell or cause a decrease in the physical strength of the membrane.
There is a liquid retention coating on the corner area of the electrode assembly, which consists of polyvinylidene fluoride and ketoanhydride-type thermoplastic polyimide. Polyvinylidene fluoride serves as a binder to bond the ketoanhydride-type thermoplastic polyimide to the ketoanhydride-type thermoplastic polyimide as a binder Attached to the surface of the negative electrode sheet, it compensates for excessive extrusion at corners and poor liquid retention ability, maintains the energy density of the battery cell and improves the processing performance of the diaphragm.
It effectively improves the lithium circulating corner lithium analysis of the battery cell, improves the circulation capacity retention rate, reduces the thickness expansion rate, and improves the kinetic performance, making up for the potential kinetic performance loss caused by the liquid retention coating.
Smart Images

Figure CN119297371A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a secondary battery with high liquid retention capacity, a preparation method thereof, and electrical equipment thereof. Background Art
[0002] As the rate performance of lithium-ion batteries improves, during the 3C and above fast charging cycle, the square soft-pack lithium-ion cells with a wound structure are squeezed tighter at the corners, and the electrolyte retention is usually poor. The lithium ion permeability will also decrease, which will easily lead to the appearance of black spots of lithium precipitation at the corners in the later stage of the cycle. In response to this problem, researchers have proposed a variety of different methods, such as increasing the thickness of the diaphragm or using a diaphragm with a higher porosity to increase the liquid retention. However, the former method will lose the energy density of the battery cell, and the latter method will easily lead to a decrease in the physical strength of the diaphragm, and higher processing performance requirements for the diaphragm. Therefore, it is necessary to propose a lithium-ion battery that does not affect the energy density of the battery cell, is easy to process, and has good liquid retention. Summary of the invention
[0003] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a secondary battery with high liquid retention capacity, a preparation method thereof, and an electrical device.
[0004] In a first aspect of the present application, a secondary battery is provided, the secondary battery comprising an electrode assembly, the electrode assembly comprising a first electrode sheet, a second electrode sheet and a separator located between the first electrode sheet and the second electrode sheet, the electrode assembly being a winding structure, the electrode assembly comprising connected corner areas and straight areas;
[0005] The second pole piece has a first surface and a second surface opposite to the first surface, and a liquid retaining coating is provided on the first surface and / or the second surface in the corner area, and the liquid retaining coating includes polyvinylidene fluoride and ketone anhydride type thermoplastic polyimide (ketone anhydride type TPI).
[0006] The secondary battery according to the first aspect of the present application has the following beneficial effects:
[0007] The main reason for the problems of tight packing at the corners, less electrolyte space, and poor liquid retention is the space squeezing caused by the expansion of the active material, especially at the corners. Therefore, the solution of the present application is different from the existing concept of changing the diaphragm structure. Instead, it selectively improves the electrode in the corner area and adds a liquid retention coating comprising polyvinylidene fluoride and ketoanhydride thermoplastic polyimide thereon, wherein the ketoanhydride thermoplastic polyimide plays a certain supporting role, and the polyvinylidene fluoride is used as a binder to adhere the ketoanhydride thermoplastic polyimide to the surface of the negative electrode, compensating for excessive squeezing at the corners and poor liquid retention capacity, with little loss in the energy density of the battery cell and no degradation in the processing performance of the diaphragm, thereby effectively improving the lithium deposition at the cycle corners of the battery cell made of the electrode, and the cycle capacity retention rate at different temperatures continues to increase, and the thickness expansion rate is reduced.
[0008] In some embodiments of the present application, the mass ratio of polyvinylidene fluoride to ketoanhydride type thermoplastic polyimide is (0.5-10):(99.5-90).
[0009] In some embodiments of the present application, the coverage of the liquid-retaining coating on the first surface or the second surface of the corner area is 10-30%.
[0010] In some embodiments of the present application, the thickness of the liquid-retaining coating is 2 to 5 μm.
[0011] In some embodiments of the present application, the coating surface density of the liquid-retaining coating is 0.2 to 1 g / m 2 .
[0012] In some embodiments of the present application, the second electrode sheet is a negative electrode sheet.
[0013] In some embodiments of the present application, the electrode assembly includes 2n corner regions starting from the winding start point;
[0014] Among them, the length L of the negative electrode sheet in the 2k+1th corner area 2k+1 =π×(r1+kT), the length of the negative electrode sheet at the 2k+2nd corner area is L 2k+2 =L 2k+1 ;
[0015] n is the number of winding layers of the negative electrode sheet, k is an integer from 0 to n-1,
[0016] r1 = diaphragm thickness × 6 + single-sided coated negative electrode sheet thickness × 0.5, r 2k+1 =r1+kT,r 2k+2 =L 2k+1 , where 35μm≤r1≤165μm;
[0017] T = diaphragm thickness × 2 + double-sided coated positive electrode sheet thickness + double-sided coated negative electrode sheet thickness, where 75μm≤T≤125μm.
[0018] In some embodiments of the present application, the length of the straight area W=W0-(r1+nT), W0 is the width of the battery cell, wherein 10 mm≤W≤300 mm.
[0019] In some embodiments of the present application, the liquid-retaining coating has a mesh-like porous structure.
[0020] In a second aspect of the present application, a method for preparing a secondary battery is provided, the method comprising the following steps:
[0021] Applying active slurry on the current collector of the second pole piece to form a semi-finished second pole piece;
[0022] The liquid retaining slurry is coated on the first surface and / or the second surface in the corner area to obtain a second pole piece, wherein the liquid retaining slurry includes polyvinylidene fluoride and ketone anhydride type thermoplastic polyimide.
[0023] According to a third aspect of the present application, an electrical device is provided, the electrical device comprising the aforementioned secondary battery.
[0024] Compared with the prior art, the embodiments of the present application have the following advantages:
[0025] 1) Without changing the diaphragm structure, only the pole piece at the corner of the battery cell is adjusted, which compensates for the poor liquid retention capacity caused by excessive extrusion at the corner, has little loss in the energy density of the battery cell, and has no degradation in the processing performance of the diaphragm;
[0026] 2) After adding the liquid-retaining coating, the lithium deposition in the corner of the battery cell cycle is improved, the cycle capacity retention rate is increased, and the thickness expansion rate is reduced;
[0027] 3) The added liquid-retaining coating has a certain improvement on the kinetic performance of the battery cell due to its increased liquid-retaining capacity and small coating coverage. The improvement in kinetic performance brought about by the liquid-retaining coating can make up for the loss in kinetic performance caused by the addition of the liquid-retaining coating. The appropriate ratio of ketoanhydride TPI and PVDF in the coating is more conducive to improving kinetic performance and reducing thickness expansion of the battery cell.
[0028] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the structure of a battery cell according to an embodiment of the present application.
[0030] Figure 2It is a schematic structural diagram of a negative electrode sheet of a battery cell according to an embodiment of the present application.
[0031] Figure 3 This is an electron microscope photograph of a negative electrode sheet made in one embodiment of the present application.
[0032] Reference numerals: first pole piece 100 , second pole piece 200 , diaphragm 300 , corner area 400 , first corner area 410 , second corner area 420 , third corner area 430 , straight area 500 , first straight area 510 , second straight area 520 , liquid retaining coating 600 . DETAILED DESCRIPTION
[0033] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0034] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.
[0035] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0036] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0037] refer to Figure 1, shows the basic structure of an electrode assembly formed by a conventional negative electrode sheet, which is a wound structure battery cell, which includes a first electrode sheet 100, a second electrode sheet 200 and a separator 300 forming a wound structure. The first electrode sheet 100 and the second electrode sheet 200 are separated by a separator 300, and the three are stacked and wound to form a wound structure. The first electrode sheet 100, the second electrode sheet 200 and the separator 300 are divided into a corner area 400 and a straight area 500 according to their different local positions in the wound structure battery cell. Accordingly, for the electrode assembly, refer to Figure 2 Combined with Figure 1 , including corner areas 400 and straight areas 500 alternately arranged in sequence along the length direction, according to the direction of the electrode assembly from the winding starting end (i.e., the innermost position after the winding structure is formed) to the winding end, the corner area 400 includes the first corner area 410, the second corner area 420, the third corner area 430, etc. arranged in sequence, and the straight area 500 includes the first straight area 510, the second straight area 520, etc. arranged in sequence. It can be understood that the naming of the first corner area 410, the first straight area 510, etc. is not directly used to limit the number of corner areas and straight areas corresponding to the first pole piece or the second pole piece. According to the actual winding situation, the number of corner areas and straight areas can be less or more, usually more, for example, more than 3, more than 4, more than 5, more than 6, more than 7, more than 8, more than 9, more than 10, etc., respectively and independently.
[0038] Generally, the lithium battery cells of the above-mentioned winding structure are more densely packed in the corner area due to the spatial compression, which leads to poor electrolyte retention and reduced lithium ion permeability, so that black spots of lithium deposition at the corners are likely to appear in the later stage of the cycle. Therefore, different from the existing solutions of changing the thickness and porosity of the diaphragm, this embodiment proposes a new type of secondary battery, referring to Figure 2 The second pole piece 200 has a first surface and a second surface opposite to the first surface, and a liquid retaining coating 600 is disposed on the first surface and / or the second surface in the corner area 400. The raw materials of the liquid retaining coating 600 include polyvinylidene fluoride and ketoanhydride type thermoplastic polyimide.
[0039] Among them, polyvinylidene fluoride refers to a polymer containing 1,1-difluoroethylene monomer, including at least one of a homopolymer of 1,1-difluoroethylene and a copolymer of 1,1-difluoroethylene. In some embodiments, in addition to 1,1-difluoroethylene, other monomers contained in the copolymer include other fluorine-containing monomers. In some specific embodiments, other fluorine-containing monomers include fluorine-containing olefin monomers, such as at least one of trifluoroethylene, tetrafluoroethylene, trifluorochloroethylene, hexafluoropropylene, etc.
[0040] Among them, polyimide (PI) refers to a class of polymers containing an imide ring on the main chain, such as a phthalimide structure. Polyimide can be divided into thermoplastic polyimide and thermosetting polyimide according to the difference in properties. Thermoplastic polyimide (TPI) can be further divided into bisphenol A type TPI, homoanhydride type TPI, ketone anhydride type TPI, ether anhydride type TPI, biphenyl anhydride type TPI, copolymer TPI, etc. according to the different types of dianhydrides. Ketone anhydride type TPI refers to TPI based on benzophenone tetraacid dianhydride (BTDA), which is synthesized by chemical cyclization method using 3,3',4,4'-benzophenone tetraacid dianhydride (BTDA) and 4,4'-diaminodiphenyl ether (ODA) as raw materials.
[0041] In the scheme of the embodiment of the present application, a liquid-retaining coating is formed with polyvinylidene fluoride and ketoanhydride thermoplastic polyimide, and the ketoanhydride thermoplastic polyimide plays a certain supporting role, while the polyvinylidene fluoride is used as a binder to adhere the ketoanhydride thermoplastic polyimide to the surface of the negative electrode sheet, compensating for the poor liquid-retaining ability due to excessive extrusion at the corners, with little loss of energy density of the battery cell, and no degradation of the processing performance of the diaphragm, thereby effectively improving the lithium precipitation at the corners of the battery cell made of the negative electrode sheet, and the cycle capacity retention rate at different temperatures continues to increase, and the thickness expansion rate is reduced. Through this concept, the design of the liquid-retaining coating increases the buffering effect and can provide a liquid-retaining space for electrolyte infiltration. In addition, the liquid-retaining coating also plays a certain bonding role.
[0042] When polyvinylidene fluoride and ketoanhydride thermoplastic polyimide are combined in different proportions, different effects will be caused on the rate performance and thickness expansion of the lithium battery made of the negative electrode sheet. Therefore, after balancing the comprehensive performance, in some embodiments, the mass ratio of polyvinylidene fluoride and ketoanhydride thermoplastic polyimide in the liquid-retaining coating is (0.5-10): (99.5-90). In some embodiments, the liquid-retaining coating is polyvinylidene fluoride and ketoanhydride type thermoplastic polyimide, the content of polyvinylidene fluoride is 0.5-10%, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, and the content of ketoanhydride type thermoplastic polyimide is 99.5-90%, for example, it can be 99.5%, 99.4%, 99.3%, 99.2%, 99.1%, 99%, 98%, 97%, 96%, 95%, 94%, 93%, 92%, 91%, 90%. In some embodiments, polyvinylidene fluoride and ketone anhydride type thermoplastic polyimide are polymers soluble in polar organic solvents, and polyvinylidene fluoride and ketone anhydride type thermoplastic polyimide are dissolved in polar organic solvents to obtain a slurry of a liquid-retaining coating. In some embodiments, the solid content of the slurry of the liquid-retaining coating is 2 to 10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0043] In some embodiments, the coverage of the liquid-retaining coating on the first surface or the second surface in the corner area is 10-30%, for example, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, or 30%.
[0044] Wherein, coverage refers to the percentage of the area of the liquid-retaining coating in the set area of the corner area. In some embodiments, the coverage of the liquid-retaining coating is 10-30%, which means that in the total area of all corner areas of the first surface of the second pole piece, for example, the total area of all corner areas including the first corner area, the second corner area (if any), the third corner area (if any), etc., the coverage of the liquid-retaining coating is 10-30%, and the coverage of the liquid-retaining coating in a specific corner area of the second pole piece is not limited. In some specific embodiments, the coverage of the liquid-retaining coating on the first surface in each corner area is 10-30%. In some embodiments, the second pole piece 200 is a negative pole piece, the first pole piece 100 is a positive pole piece, and the first surface of the second pole piece in the corner area has a liquid-retaining coating. In some embodiments, such as Figure 2 As shown, the liquid retaining coating 600 is located on the first surface of the corner region 400 of the second pole piece 200. In other embodiments, both surfaces (ie, the first surface and the second surface opposite to the first surface) of the corner region 400 of the second pole piece 200 contain liquid retaining coatings.
[0045] In some embodiments, the liquid-retaining coating has a mesh-like porous structure.
[0046] In some embodiments, the thickness of the liquid-retaining coating is 2-5 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm. The thickness of the liquid-retaining coating affects the coating area density of the liquid-retaining coating. 2 , for example, it can be 0.2g / m 2 , 0.3g / m 2 , 0.4g / m 2 , 0.5g / m 2 , 0.6g / m 2 , 0.7g / m 2 , 0.8g / m 2 , 0.9g / m 2 , 1g / m 2 .
[0047] In some embodiments, the electrode assembly comprises 2n corner regions starting from the winding start point;
[0048] Among them, the length L of the negative electrode sheet in the 2k+1th corner area2k+1 =π×(r1+kT), the length of the negative electrode sheet at the 2k+2nd corner area is L 2k+2 =L 2k+1 ;
[0049] n is the number of winding layers of the negative electrode sheet, k is an integer from 0 to n-1,
[0050] r1 = diaphragm thickness × 6 + single-sided coated negative electrode sheet thickness × 0.5, r 2k+1 =r1+kT,r 2k+2 =L 2k+1 , where 35μm≤r1≤165μm;
[0051] T = diaphragm thickness × 2 + double-sided coated positive electrode sheet thickness + double-sided coated negative electrode sheet thickness, where 75μm≤T≤125μm.
[0052] In some embodiments, the length of the straight region W=W0-(r1+nT), W0 is the width of the battery cell, wherein 10 mm≤W≤300 mm.
[0053] In some embodiments, the negative electrode sheet includes a negative electrode current collector, a negative electrode active material layer, and a liquid retaining coating located in a corner area, which are arranged in sequence. The liquid retaining coating is located on the side of the negative electrode active material layer away from the negative electrode current collector. In some embodiments, only one side of the negative electrode current collector has a negative electrode active material layer, and accordingly, the liquid retaining coating is also only located on the side of the negative electrode active material layer away from the negative electrode current collector. In some other embodiments, both sides of the negative electrode current collector have a first negative electrode active material layer and a second negative electrode active material layer, and accordingly, the liquid retaining coating includes a first liquid retaining coating located on the side of the first negative electrode active material layer away from the negative electrode current collector and a second liquid retaining coating located on the side of the second negative electrode active material layer away from the negative electrode current collector. The first liquid retaining coating and the second liquid retaining coating, as well as the types and proportions of polyvinylidene fluoride and ketoanhydride type thermoplastic polyimide in the liquid retaining coating in different corner areas may be the same or different.
[0054] In some embodiments, the negative electrode active material of the negative electrode active material layer on the negative electrode sheet is any one of a silicon material, a carbon material, and a silicon-carbon composite material. The carbon material includes at least one of graphite (such as natural graphite, artificial graphite), hard carbon, and soft carbon. The silicon material includes at least one of elemental silicon, silicon oxide compounds, and silicon alloys.
[0055] In some embodiments, the raw material of the negative electrode active material layer further includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT) and graphene, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc.
[0056] In some embodiments, the negative electrode active material layer includes 70 to 99 wt % of the negative electrode active material, 0.5 to 6 wt % of the conductive agent, and 0.5 to 20 wt % of the binder.
[0057] In some embodiments, when the negative electrode active material, the conductive agent and the binder are made into the negative electrode active material layer, the active material, the conductive agent and the binder are dispersed in a solvent, coated on the negative electrode current collector, and dried to obtain the negative electrode active material layer.
[0058] In some embodiments, the secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet, the negative electrode sheet and the separator are wound to obtain a battery cell and made into a lithium-ion battery.
[0059] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer.
[0060] In some embodiments, the positive electrode current collector and the negative electrode current collector are independently selected from at least one of metal materials including metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or alloy foil of the above metals), metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or alloy mesh of the above metals).
[0061] In some embodiments, the positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.
[0062] In some embodiments, the positive electrode active material layer includes a positive electrode active material, which is at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium nickel manganese aluminum oxide.
[0063] In some embodiments, the raw material of the positive electrode active material layer also includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT) and graphene, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc.
[0064] In some embodiments, the positive electrode active material layer includes 70 to 99 wt % of the positive electrode active material, 0.5 to 6 wt % of the conductive agent, and 0.5 to 20 wt % of the binder.
[0065] In some of the embodiments, the electrolyte may be at least one of a solid electrolyte or an electrolyte solution.
[0066] In a second aspect of the present application, a method for preparing a secondary battery is provided, comprising the following steps:
[0067] Applying active slurry on the current collector of the second pole piece to form a semi-finished second pole piece;
[0068] The liquid retaining slurry is applied to the first surface and / or the second surface of the corner area by spraying to obtain a second pole piece, wherein the liquid retaining slurry includes polyvinylidene fluoride and ketone anhydride type thermoplastic polyimide.
[0069] In some embodiments, the negative electrode active slurry includes a negative electrode active material. In some specific embodiments, the negative electrode active slurry also includes at least one of a conductive agent and a binder. In some specific embodiments, the negative electrode active slurry also includes a solvent.
[0070] In some of the embodiments, the spraying method is intermittent rotary spraying. The liquid-retaining coating formed in this way can effectively increase the liquid-retaining space, and the coating device does not contact the negative electrode sheet, and there is no mechanical damage to the negative electrode sheet.
[0071] In some embodiments, the semi-finished negative electrode sheet is composed of a negative electrode active material layer formed of a negative electrode current collector and a negative electrode active slurry.
[0072] The third aspect of the present application provides an electrical device. The electrical device includes the aforementioned lithium-ion battery. Among them, the electrical device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy, or other one or more energy-forming devices, such as electric motors, electric heat engines, electric light sources, etc. Among them, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. are included. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0073] The present application is described below in conjunction with specific examples. The raw materials used in the examples and comparative examples can all be purchased commercially. Among them, the number average molecular weight of ketoanhydride TPI is 20,000 to 30,000, and the glass transition temperature measured by DSC is 270 to 276°C. The brand of vinylidene fluoride homopolymer is Kynar HSV 900, and the brand of vinylidene fluoride-hexafluoropropylene copolymer is Kynar LBG.
[0074] Example 1
[0075] This embodiment provides a secondary battery, which includes a negative electrode sheet, the negative electrode sheet includes a copper foil current collector and a negative electrode active material layer located on the copper foil current collector. The negative electrode sheet has a first surface and a second surface opposite to each other, and a liquid retaining coating is provided on the first surface in the corner area. The specific preparation process is as follows:
[0076] (1) Acetone was added to a double planetary mixer, followed by the addition of ketoanhydride-type thermoplastic polyimide, which was stirred until dissolved, followed by the addition of vinylidene fluoride homopolymer powder (denoted as PVDF-1), which was stirred until dissolved to prepare a liquid-retaining coating slurry with a solid content of 10%, wherein the mass ratio of ketoanhydride-type TPI to PVDF-1 was 9:1.
[0077] (2) Graphite, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and carbon black conductive agent are mixed in a mass ratio of 97.8:0.6:0.6:1 and stirred with deionized water to form a negative electrode slurry. The negative electrode slurry is coated on copper foil, and after drying, it is rolled to form a semi-finished negative electrode sheet. Then, the liquid-retaining coating slurry prepared in step (1) is coated on the corner area of the semi-finished negative electrode sheet by intermittent rotary spraying, and after drying, it is cut into negative electrode sheets. Among them, the thickness of the liquid-retaining coating is 3μm, and the surface density of the coating is 0.5g / m 2 .
[0078] The coating morphology of the negative electrode sheet is referenced Figure 3It can be seen that the liquid-retaining coating on the first surface of the negative electrode sheet in the corner area is a mesh porous structure. According to the area of the liquid-retaining coating on the first surface and the total area of the first surface in the corner area, the coverage of the liquid-retaining coating is 15%.
[0079] The secondary battery of this embodiment also involves the preparation of a positive electrode sheet, an electrolyte, etc., and the process is as follows:
[0080] (1) The positive electrode active material lithium cobalt oxide, the conductive agent (SP and CNT mixed at a mass ratio of 0.45:0.05), and the binder (SBR and PAALi mixed at a mass ratio of 0.5:1.8) were mixed at a weight ratio of 97.7:1.1:1.2, and stirred with the solvent NMP to obtain a positive electrode slurry. The positive electrode slurry was coated on the positive electrode current collector aluminum foil, dried, and cut into positive electrode sheets.
[0081] (2) Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 2:4:4 to obtain an organic solvent, and then lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0082] (3) The diaphragm is a PE-based film coated with an alumina coating and a double-sided oil-based PVDF coating. The positive electrode sheet, the negative electrode sheet, and the diaphragm are wound into a core, which is sealed in an aluminum-plastic film and injected with electrolyte to produce a 4.5V, 5Ah battery cell.
[0083] Example 2
[0084] This embodiment provides a secondary battery, which is different from the embodiment 1 in that the mass ratio of ketoanhydride TPI to PVDF-1 in the liquid retaining coating is 99.5:0.5.
[0085] Example 3
[0086] This embodiment provides a secondary battery, which is different from the embodiment 1 in that the mass ratio of ketoanhydride TPI to PVDF-1 is 95:5.
[0087] Example 4
[0088] This embodiment provides a secondary battery. The difference between the current collector and the embodiment 1 is that the coverage rate of the liquid retaining coating in the corner area is 10%.
[0089] Example 5
[0090] This embodiment provides a secondary battery. The difference between the current collector and the embodiment 1 is that the coverage rate of the liquid retaining coating in the corner area is 30%.
[0091] Example 6
[0092] This embodiment provides a secondary battery, which is different from the embodiment 1 in that the vinylidene fluoride homopolymer in the liquid retaining coating is replaced by a vinylidene fluoride-hexafluoropropylene copolymer (denoted as PVDF-2) of equal mass.
[0093] Comparative Example 1
[0094] This comparative example provides a secondary battery, which is different from Example 1 in that there is no liquid-retaining coating on the negative electrode sheet.
[0095] Comparative Example 2
[0096] This comparative example provides a secondary battery, which is different from Example 1 in that the preparation method of the liquid-retaining coating is as follows: ketoanhydride TPI and PVDF-1 are added to an organic solvent in a mass ratio of 9:1 to prepare a spinning solution, and a fiber spinning layer with a thickness of 8 μm is formed at the corner of the first surface of the semi-finished negative electrode sheet by electrospinning, and then the negative electrode sheet is cut into pieces after drying.
[0097] Comparative Example 3
[0098] This comparative example provides a secondary battery, which is different from Example 1 in that the ketoanhydride-type TPI is replaced by an equal mass of bisphenol A-type TPI.
[0099] Comparative Example 4
[0100] This comparative example provides a secondary battery, which is different from Example 1 in that PVDF-1 is replaced by PMMA of equal mass.
[0101] Comparative Example 5
[0102] This comparative example provides a secondary battery, which is different from Example 1 in that the coverage of the liquid-retaining coating in the corner area is 5%.
[0103] Comparative Example 6
[0104] This comparative example provides a secondary battery, which is different from Example 1 in that the coverage of the liquid-retaining coating in the corner area is 50%.
[0105] Comparative Example 7
[0106] This comparative example provides a secondary battery, which is different from Example 1 in that the liquid-retaining coating completely covers the first surface of the corner area.
[0107] Comparative Example 8
[0108] This comparative example provides a secondary battery, which is different from Example 1 in that the mass ratio of ketoanhydride TPI to PVDF-1 is 99.7:0.3.
[0109] Comparative Example 9
[0110] This comparative example provides a secondary battery, which is different from Example 1 in that the mass ratio of ketoanhydride TPI to PVDF-1 is 85:15.
[0111] The performance of the negative electrode sheets and lithium batteries of the embodiments and comparative examples were tested by the following methods:
[0112] (1) The liquid retention coefficient is calculated according to the following formula: Liquid retention coefficient = (liquid injection volume - secondary sealing liquid loss volume) / battery cell capacity.
[0113] (2) The cell energy density is calculated according to the following formula: cell energy density = cell capacity × 3.9 V / (cell length × width × thickness). 3.9 V is the platform voltage.
[0114] (3) The rate discharge is calculated according to the following formula: rate discharge = discharge capacity at corresponding rate / 0.2C discharge capacity × 100%.
[0115] (4) Thickness expansion rate at 85°C for 6 hours: After fully charging the battery cell, test the initial thickness d0; then place the battery cell in an 85°C constant temperature box for 6 hours, and then place it at room temperature for 2 hours. After cooling, test the thickness d1. The expansion rate = (d1-d0) / d0×100%.
[0116] (5) Normal temperature cycle: In a 25±2℃ constant temperature box, charge to 4.2V at 3C constant current and constant voltage, cut-off current 2C, charge to 4.35V at 2C constant current and constant voltage, cut-off current 1.5C, charge to 4.5V at 1.5C constant current and constant voltage, cut-off current 0.05C, and leave for 5 minutes; discharge to 3V at 1C constant current, record discharge capacity Cn, discharge capacity Cn / initial capacity C0 is the capacity retention rate of the nth week. The full charge thickness of the test cell before cycling is d0, and the full charge thickness of the test cell is dn every 100 weeks, and the thickness expansion rate = (dn-d0) / d0.
[0117] (6) 45℃ cycle: In a 45±2℃ constant temperature box, charge to 4.2V at 3C constant current and constant voltage, cut-off current 2C, charge to 4.35V at 2C constant current and constant voltage, cut-off current 1.5C, charge to 4.5V at 1.5C constant current and constant voltage, cut-off current 0.05C, and leave for 5min; discharge to 3V at 1C constant current, record discharge capacity Cn, discharge capacity Cn / initial capacity C0 is the capacity retention rate of the nth week. The full charge thickness of the cell tested before the cycle is d0. After every 100 cycles, the cell is placed in a 25±2℃ environment for 2h, and the full charge thickness dn of the cell is tested. The thickness expansion rate = (dn-d0) / d0×100%.
[0118] The results are shown in Table 1:
[0119] Table 1. Performance test results of examples and comparative examples
[0120]
[0121] Comparing Example 1 with Comparative Example 1, Example 1 adds a liquid-retaining coating in the corner area of the negative electrode sheet, the liquid-retaining capacity of the battery cell is improved, and the energy density of the battery is basically not lost, the discharge performance at 2C and above rates is improved, the thickness expansion rate at 85°C high-temperature storage is smaller, and the cycle capacity attenuation and thickness expansion at 45°C and room temperature conditions are also smaller.
[0122] Comparing Examples 1, 2 and 3, increasing the ratio of TPI:PVDF in the liquid-retaining coating is more conducive to improving the rate performance and reducing the cycle capacity decay at 45°C and room temperature, but when the PVDF ratio is higher, the energy density, high-temperature storage and cycle thickness expansion rate are smaller. At the same time, combined with Comparative Examples 8 and 9, when the ratio of TPI:PVDF is too low or too high, the thickness expansion rate at 85°C high-temperature storage increases, and the cycle capacity decay and thickness expansion at 45°C and room temperature will become larger.
[0123] Comparing Examples 1, 4 and 5, as the coverage of the liquid-retaining coating in the corner area increases from 10% to 30%, the liquid-retaining capacity, energy density and rate performance of the battery cell decrease accordingly, but the cycle thickness expansion at 45°C and room temperature also decreases accordingly, and the cycle capacity attenuation shows a trend of first decreasing and then increasing. In addition, combined with the comparison of Comparative Example 7, Comparative Example 5, Comparative Example 6 and Example 1, when the coverage is too low or too high, the thickness expansion rate of 85°C high-temperature storage increases, and the cycle capacity attenuation and thickness expansion at 45°C and room temperature will increase. For example, in Comparative Example 7, when the liquid-retaining coating is applied to the entire surface of the negative electrode sheet, the energy density of the battery cell is greatly reduced, and the rate performance and storage thickness expansion at high temperature and room temperature are not as good as those in Example 1.
[0124] Comparing Example 1 and Example 6, the type of polyvinylidene fluoride used in the liquid retaining coating is changed, and the liquid retaining performance, energy density and rate performance remain basically unchanged. However, the thickness expansion rate of high-temperature storage at 85°C and the cyclic capacity attenuation and thickness expansion at 45°C and room temperature conditions have changed, which are higher when polyvinylidene fluoride-hexafluoropropylene copolymer is used.
[0125] Comparing Comparative Example 2 and Example 1, the liquid-retaining layer formed by the electrospinning method has an improvement effect that is not as good as the liquid-retaining coating provided in Example 1, which is mainly manifested in a larger storage thickness expansion, and the cycle capacity retention rate and thickness expansion are both worse than those in Example 1.
[0126] Comparing Comparative Example 1, Comparative Example 3, Comparative Example 4 and Example 1, when polyvinylidene fluoride in the liquid retaining coating is replaced by polymethyl methacrylate, or ketoanhydride-type thermoplastic polyimide is replaced by other types of polyimide, the liquid retaining performance, energy density, and rate performance are basically equivalent to those of Comparative Example 1 without a liquid retaining coating, and are significantly different from Example 1; at the same time, the thickness expansion at room temperature is even higher than that of Comparative Example 1; and the thickness expansion rate of high-temperature storage at 85°C and the cyclic capacity attenuation and thickness expansion at 45°C are lower than those of Comparative Example 1, but are also significantly lower than those of Example 1.
[0127] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
Claims
1. A secondary battery, characterized in that: The secondary battery comprises an electrode assembly, the electrode assembly comprises a first electrode sheet, a second electrode sheet and a separator located between the first electrode sheet and the second electrode sheet, the electrode assembly is a winding structure, and the electrode assembly comprises connected corner areas and straight areas; The second pole piece has a first surface and a second surface opposite to the first surface, and the first surface and / or the second surface in the corner area are provided with a liquid retaining coating, and the liquid retaining coating includes polyvinylidene fluoride and ketoanhydride type thermoplastic polyimide.
2. The secondary battery according to claim 1, characterized in that: The mass ratio of the polyvinylidene fluoride to the ketone anhydride type thermoplastic polyimide is (0.5-10):(99.5-90).
3. The secondary battery according to claim 1, characterized in that: The coverage rate of the liquid-retaining coating on the first surface or the second surface of the corner area is 10-30%.
4. The secondary battery according to claim 1, characterized in that: The thickness of the liquid-retaining coating is 2 to 5 μm, and the coating surface density of the liquid-retaining coating is 0.2 to 1 g / m 2 .
5. The secondary battery according to claim 1, characterized in that: The second electrode sheet is a negative electrode sheet.
6. The secondary battery according to claim 5, characterized in that: The electrode assembly comprises 2n corner regions starting from the winding starting point; The length L of the negative electrode sheet at the 2k+1th corner region is 2k+1 =π×(r1+kT), the length L of the negative electrode sheet at the 2k+2nd corner area 2k+2 =L 2k+1 ; n is the number of winding layers of the negative electrode sheet, k is an integer from 0 to n-1, r1 = diaphragm thickness × 6 + single-sided coated negative electrode sheet thickness × 0.5, r 2k+1 =r1+kT,r 2k+2 =L 2k+1 , where 35μm≤r1≤165μm; T = diaphragm thickness × 2 + double-sided coated positive electrode sheet thickness + double-sided coated negative electrode sheet thickness, where 75μm≤T≤125μm.
7. The secondary battery according to claim 6, characterized in that: The length of the straight area W=W0-(r1+nT), W0 is the width of the battery cell, wherein 10mm≤W≤300mm.
8. The secondary battery according to claim 1, characterized in that: The liquid-retaining coating has a mesh-like porous structure.
9. The method for preparing a secondary battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: Applying active slurry on the current collector of the second pole piece to form a semi-finished second pole piece; The second pole piece is obtained by coating the liquid retaining slurry onto the first surface and / or the second surface in the corner area, wherein the liquid retaining slurry comprises polyvinylidene fluoride and ketone anhydride type thermoplastic polyimide.
10. Electrical equipment, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 8.